Western Season with Epidemic Flu, SARS-CoV-2 Omicron Strains and hRSV - Tarro, Giulio (British Journal of Healthcare and Medical Research, 2023)
Last Fall/Winter season there was not only the ghost of COVID-19 in circulation, but many other respiratory microbic agents were present with the return of influenza viruses and of the RSV, also it is worthy to mention the adenoviruses family and even the streptococcus haemolytic. The main reason of this paper is the description of what happened with the final goal to be prepared for an early diagnosis and a prompt therapy that put in primis the prevention with specific vaccines when there is the possibility.